Analisis Tingkat Kepuasan Konsumen Rumah Tradisional Minahasa di Kecamatan Tomohon - Hibert, Tineke (JBE (Journal of Business and Economics), 2003)
The Minahasa traditional home industries a kind of small industry that usually produces a Minahasan traditional house. From time to time the demand of this product is so increasingly and in line with the demand, there are many new companies coming out. Problem may be raised form the competition such as: what factors that should be paid attention order to compete in the market place. Method of analysis to be used in this study is descriptive analysis and variables to be measured is the customer satisfaction, with indicators: product quality, design, and the coverage of product. The result of this research showed that price was more significantly influence to the customer satisfaction.